Analisis Pengaruh Konsentrasi Loss circulation material Terhadap Kinerja Permeability plugging test pada Synthetic Oil-Based Mud: Studi Kasus Sumur ZR - Azahrah Qurratu Ain Azmi; Joko Wiyono; Abdi Suprayitno (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Lost circulation is a critical drilling problem that causes drilling fluid to enter the formation, triggering wellbore instability and higher operational costs. In the ZR Well, a severely depleted zone (1.7 ppg) at approximately 7,200 ft depth carries a high risk of total circulation loss. This study evaluates the effectiveness of various concentrations of multimodal Loss circulation material (LCM), combining Safecarb, Quick seal fine, and G-seal plus, in reducing fluid loss in a 10.5 ppg Synthetic Oil-Based Mud system. The method used secondary data from Permeability plugging test (PPT) results under HTHP conditions (280°F, 2,000 psi differential pressure, 60-micron ceramic disk) with total additive concentrations ranging from 2.5 to 10 ppb. Results show that increasing LCM concentration consistently reduced filtrate volume, with the best performance at 10 ppb (spurt loss 1.0 mL; total fluid loss 8.2 mL), producing a thin, dense, and impermeable filter cake. The 10 ppb formulation is recommended as the optimal solution for mitigating loss circulation in the ZR Well.